Technological Options Selection to Produce Ferric Chloride Using Analytic Hierarchy Process Enhanced with Fuzzy Logic - Oddershede-Herrera, A; Olivares-Chiappa, V (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a method to characterize, select and evaluate technological options to produce ferric chloride. The methodology uses AHP (Analytic Hierarchy Process) enhanced with fuzzy logic (FEAHP). With this methodology it is possible to include the vagueness associated with the evaluators in the decision making to evaluate a new business and select technologies. Producing ferric chloride will reduce or eliminate effluents from the molybdenum production process, such as ferrous chloride, reducing environmental contamination of the process and achieving a potential new business. A model was designed using existing literature on AHP, FEAHP and other assessment tools to select technologies and evaluate new businesses that reduce environmental impact. The model was validated using a case study related to using ferrous chloride, which is an effluent from the molybdenum leaching process, producing ferric chloride that can be transformed into a new business with the benefit of reducing environmental pollution. By applying the extended AHP method with fuzzy logic to model the uncertainty of the experts regarding the comparative judgments, the analysis performed in this work allowed to discard technological options to reprocess the ferrous chloride and to obtain ferric chloride, leaving finally two options that were the alternatives with greater weight, which later were evaluated economically. The method facilitates decision making regarding the selection or prioritization of technologies to evaluate new business in environmentally sensitive areas. The contribution of this work is the proposed method based in FEAHP to select technologies to produce a product and open a new market. The method allowed selecting options of technology in a rare business with great environmental impact for the zone. In the case study the results indicated the desirability of not increasing the production by more than 25%, discarding, for example, options of doubling the production because of the environmental risks. © 2018 IEEE.